'Everything is Plastic' The Faith of Unity Movement and the Making of a Post-Catholic Religion in Uganda - Ukah, Asonzeh Franklin-Kennedy 1965- (2018)
One of David Chidester's long-term fascinations in the academic study of religion is his nuanced scrutiny of the sensorial features of contemporary religious life. Chidester uses an approach of multi-sensorial imagination of matter to investigate the plasticity and elasticity of religion to innovate and accommodate changing religious and spiritual desires and how such adaptions ensure the popularity of religious participation in a contemporary, technology-saturated society. Based on an ethnographic investigation of a new religious movement in Uganda, this essay mobilizes some of the analytical concepts developed by Chidester to think through the material dynamics of African religious life in the context of changing socio-economic, cultural, and political contexts of Africa.
Keywords: African Religion; David Chidester; Faith of Unity; Owobusobozi; Material Religion; post-Catholic